Evaluating New Compounds to Treat Burkholderia pseudomallei Infections - Ross, Brittany N.; Myers, Julia N.; Muruato, Laura A.; Tapia, Daniel; Torres, Alfredo G. (Frontiers in Cellular and Infection Microbiology, 2018)
Burkholderia pseudomallei is the causative agent of melioidosis, a disease that requires long-term treatment regimens with no assurance of bacterial clearance. Clinical isolates are intrinsically resistant to most antibiotics and in recent years, isolates have been collected that display resistance to frontline drugs. With the expanding global burden of B. pseudomallei, there is a need to identify new compounds or improve current treatments to reduce risk of relapse. Using the Pathogen Box generated by Medicines for Malaria Venture, we screened a library of 400 compounds for bacteriostatic or bactericidal activity against B. pseudomallei K96243 and identified seven compounds that exhibited inhibitory effects. New compounds found to have function against B. pseudomallei were auranofin, rifampicin, miltefosine, MMV688179, and MMV688271. An additional two compounds currently used to treat melioidosis, doxycycline and levofloxacin, were also identified in the screen. We determined that the minimal inhibitory concentrations (MIC) for levofloxacin, doxycycline, and MMV688271 were below 12 µg/ml for 5 strains of B. pseudomallei. To assess persister frequency, bacteria were exposed to 100x MIC of each compound. Auranofin, MMV688179, and MMV688271 reduced the bacterial population to an average of 4.53 x10-6% compared to ceftazidime, which corresponds to 25.1% survival. Overall, our data demonstrates that auranofin, MMV688197, and MMV688271 have the potential to become repurposed drugs for treating melioidosis infections and the first evidence that alternative therapeutics can reduce B. pseudomallei persistence.